Cukurici Höyük 3 Ein frühbronzezeitliches Metallhandwerkerzentrum in Westanatolien - Mehofer, Mathias (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
This work focuses on the interdisciplinary analysis of the metallurgical remains from the Tell Çukuriçi Höyük (Western Turkey), dating from the Late Chalcolithic to the Early Bronze Age (c. 3300-2700 BC). The rich ensemble of finds includes almost all parts of the technological chain (chaîne opératoire), from ore, raw metal, ingots to finished products, tin bronze and precious metals, everything is present. A concluding holistic view makes it possible to gain in-depth knowledge on the metal craft and its embedding in Early Bronze Age exchange and societal systems.